Colony growth and biofilm formation of Aspergillus niger under simulated microgravity - Cortesão, Marta; Holland, Gudrun; Schütze, Tabea; Laue, Michael; Moeller, Ralf; Meyer, Vera (Frontiers in Microbiology, 2022)
The biotechnology- and medicine-relevant fungus Aspergillus niger is a common colonizer of indoor habitats such as the International Space Station (ISS). Being able to colonize and biodegrade a wide range of surfaces, A. niger can ultimately impact human health and habitat safety. Surface contamination relies on two key-features of the fungal colony: the fungal spores, and the vegetative mycelium, also known as biofilm. Aboard the ISS, microorganisms and astronauts are shielded from extreme temperatures and radiation, but are inevitably affected by spaceflight microgravity. Knowing how microgravity affects A. niger colony growth, in particular regarding the vegetative mycelium (biofilm) and spore production, will help prevent and control fungal contaminations in indoor habitats on Earth and in space. Because fungal colonies grown on agar can be considered analogues for surface contamination, we investigated A. niger colony growth on agar in normal gravity (Ground) and simulated microgravity (SMG) conditions by fast-clinorotation. Three strains were included: a wild-type strain, a pigmentation mutant (ΔfwnA), and a hyperbranching mutant (ΔracA). Our study presents never before seen scanning electron microscopy (SEM) images of A. niger colonies that reveal a complex ultrastructure and biofilm architecture, and provide insights into fungal colony development, both on ground and in simulated microgravity. Results show that simulated microgravity affects colony growth in a strain-dependent manner, leading to thicker biofilms (vegetative mycelium) and increased spore production. We suggest that the Rho GTPase RacA might play a role in A. niger’s adaptation to simulated microgravity, as deletion of ΔracA leads to changes in biofilm thickness, spore production and total biomass. We also propose that FwnA-mediated melanin production plays a role in A. niger’s microgravity response, as ΔfwnA mutant colonies grown under SMG conditions showed increased colony area and spore production. Taken together, our study shows that simulated microgravity does not inhibit A. niger growth, but rather indicates a potential increase in surface-colonization. Further studies addressing fungal growth and surface contaminations in spaceflight should be conducted, not only to reduce the risk of negatively impacting human health and spacecraft material safety, but also to positively utilize fungal-based biotechnology to acquire needed resources in situ.